Pre Stack Depth Migration: Case Study of Seismic 3D Offshore Data - RAHADIAN A. (NIM : 12405009), M.
On a sub-surface structure with quite variations in lateral velocity and well-distributed fault, it needs a method to facilitate a better subsurface image which in the end it will helps to give a better interpretation in depth domain. Therefore, we are using PSDM method to facilitate it and hopefully, there would be a significant improvement in subsurface image and velocity model compare to PSTM method in time domain. In this case, I used an offshore 3D seismic data. In previous process, PSTM method was already performed and next step is to use the PSDM method with inputs: 3D PSTM section, CMP Gather, and RMS velocity. The sub-surface image of PSTM is good enough in showing fault image and reflectors. We also can see a flat CMP gather and a really good velocity model in vertical perspective in this step. Then, with these inputs, the 3D Kirchhoff PSDM method was performed on specific in-lines and cross-lines until we got the PSDM section in depth domain. It was also being performed an updating velocity interval in depth domain using horizon based Tomography. In general, PSDM method gives better images. Depth migrated gather of PSDM is flatter compared to CMP gather in time domain of PSTM. Laterally, there is a significant change of interval velocity after PSDM method being performed. Thus, we can conclude that PSDM method can give a better subsurface image to interpret compare to PSTM method and can show a difference lateral resolution in depth domain